NEW PRODUCT DEVELOPMENT: REASONS AND MARKETING STRATEGIES TOWARDS CUSTOMER SATISFACTION (A Case Study of Dangote Nigeria Plc, North-East Zonal Office, Maiduguri Borno State) - Odua, Abdulfatah (BW Academic Journal, 2022)
The study titled: New Product Development: reasons and Marketing Strategy (A Case Study of Dangote Nigeria Plc, North-East Zonal Office, Maiduguri, Borno State) was carried out to find out what constitute new product by looking at the attributes that constitute a product, the reasons why organizations introduce new products/service into the market other than for profit making which is the general belief by many and the various marketing strategies that are applied to the products right from when it is introduced into the market up to the decline stage of the product. The study adopted the survey research design where six (6) respondents from Dangote Zonal Office where randomly and proportionately issued with questionnaires. The finding revealed customer need, want and taste are not usually seek before production, again, it revealed that organizations do not plan there marketing strategy for there products. The study concluded by recommending among others that organizations should seek consumer need, want and taste before embarking on production, management should have planned marketing strategy for the product at all level of its life which will include withdrawing bad brands, improve upon them, rename them to reflect improvement on them.